Kinetics, transport, and structure in hard and soft materials - Green, Peter F. (Taylor and Francis, 2004)
Kinetics, Transport, and Structure in Hard and Soft Materials discusses the connection between the mechanisms of transport of atomic, or molecular entities that occur in a diverse range of materials, and structure. The text is divided into four parts. Part I discusses the fundamentals of diffusional transport (Tools), establishing the foundation for the discussions in Parts II and III on the mechanisms of transport in crystalline materials and in structurally disordered materials. Part IV analyzes phenomena such as spinodal decomposition, Mullins-Sekerka instabilities, and other types of instabilities that lead to morphological evolution facilitated by long-range collective motions of structural entities.